(untitled) (Revista de História da UEG (REVHIST), 2020)
This article aims to understand and explain the escapes of enslaved Africans on the northern Amazonian border (currently the State of Amapá) during the second half of the 18th century. Documents transcribed from the public archives of Pará and from the overseas historical archive were used to identify the survival tactics of the black workers who lived in the village of São José de Macapá and those who worked on the construction of the São José fortress. Fugitives created several strategies to escape and to remain in protection in hovels. The main escape route was directed to the Araguari River for two main factors: the geography composed by forests and rivers, as well as, the territory was disputed between Portugal and France, which generated little control in the region in dispute. Keywords: Africans. Enslaved. Escapes. Macapa. Quilombos.